Moving towards clinical trials for mitochondrial diseases. Issue 1 (2nd September 2020) - Pitceathly, Robert D.S.; Keshavan, Nandaki; Rahman, Joyeeta; Rahman, Shamima
Abstract: Primary mitochondrial diseases represent some of the most common and severe inherited metabolic disorders, affecting ~1 in 4, 300 live births. The clinical and molecular diversity typified by mitochondrial diseases has contributed to the lack of licensed disease‐modifying therapies available. Management for the majority of patients is primarily supportive. The failure of clinical trials in mitochondrial diseases partly relates to the inefficacy of the compounds studied. However, it is also likely to be a consequence of the significant challenges faced by clinicians and researchers when designing trials for these disorders, which have historically been hampered by a lack of natural history data, biomarkers and outcome measures to detect a treatment effect. Encouragingly, over the past decade there have been significant advances in therapy development for mitochondrial diseases, with many small molecules now transitioning from preclinical to early phase human interventional studies. In this review, we present the treatments and management strategies currently available to people with mitochondrial disease. We evaluate the challenges and potential solutions to trial design and highlight the emerging pharmacological and genetic strategies that are moving from the laboratory to clinical trials for this group of disorders.